What are the priorities of bureaucrats? Evidence from conjoint experiments with procurement officials - Janne Tukiainen; Sebastian Blesse; Albrecht Bohne; Leonardo M. Giuffrida; Jan Jäässkeläinen; Ari Luukinen; Antti Sieppi (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
A well-functioning bureaucracy is a precondition for efficient public goods provision. However, bureaucratic decision-making is still largely seen as a black box. We provide novel insights into the preferences of bureaucrats regarding their work outcomes. We focus on a major public sector activity and survey more than 900 real-life procurement officials in Finland and Germany. The questionnaire includes hypothetical choice experiments to study the relative importance of multiple features in tender outcomes. First, bureaucrats state to have substantial discretion at work but no important incentives. Second, our experimental results show that procurers are particularly worried about avoiding negative risks concerning prices and supplier reputation. Third, an avoidance of bidders with prior bad performance appears to be an extremely important factor. Fourth, procurers value a certain degree of competition, while litigation concerns and regional favoritism play only a small role.The striking lack of heterogeneous effects points towards the role of intrinsic motivation among public buyers in countries with high public sector capacity.
Keywords: D73; D90; H11; H57; H83; K41; M54; 330; Bureaucrats; Public Procurement; Preferences; Intrinsic Motivation; Conjoint Experiment